PEMANFAATAN ABU JENJANG KELAPA SAWIT SEBAGAI SUMBER K PADA TANAH GAMBUT DAN PENGARUHNYA TERHADAP PRODUKSI JAGUNG - Teguh Budi Prasetyo (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2009)
This research was conducted in Green House at Agriculture Faculty of Andalas University from September 2000 to Maret 2001. The objective of the research was to study of the ash of oil palm stem as K source and to determine optimum level to corn production on peat soils. The experiment was designed on Complete Randomized Design with 9 treatments and 3 replications. The treatments consisted of without oil palm ash, 100, 200, 400, 600, 800 kg/ha and 100, 200 kg KCl/ha. The result showed that application of the ash of oil palm can increase pH and K soil content. The highest pH and K soil content was obtained with 1000 kg ash/ha namely 5,56 and 5,28 me/100 g. Application 400kg ash/ha can substitute 200 kg KCl/ha. The highest corn yield was obtained with application 800kg ash/ha but not significantly with application 400 and 600 kg/haKey words: ash, K resource, corn production